Evaluation of the Implementation of Minimum Service Standards (MSS) Based on Minister of Health Regulation No. 06 of 2024 at Dandy Dinda Primary Clinic, Deli Serdang Regency - Julisda Nasution; Felix Kasim; Sri Melda Br Bangun (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2026)
The implementation of Minimum Service Standards (MSS) serves as a policy instrument designed to ensure equitable quality of primary healthcare services. However, the implementation of MSS in first-level healthcare facilities continues to face various challenges, particularly those related to the readiness and capacity of supporting systems. This study aims to evaluate the implementation of MSS at Dandy Dinda Primary Clinic in Deli Serdang Regency, assess the availability of facilities and infrastructure, and identify the supporting and inhibiting factors influencing the achievement of MSS indicators. This study employed a qualitative approach with a case study design. Data were collected through in-depth interviews, direct observations, and document analysis involving clinic management and healthcare personnel. The data were analyzed thematically by linking empirical findings to systems theory and the Donabedian model, which encompasses input, process, and output components. The findings indicate that MSS implementation at Dandy Dinda Primary Clinic has been carried out; however, it has not yet reached an optimal level. In terms of input, information systems, human resource development, and the availability of facilities and infrastructure remain insufficient to fully support MSS implementation. In the process aspect, the application of standard operating procedures is inconsistent, and quality evaluation has not been conducted routinely nor in a data-driven manner. Meanwhile, in the output aspect, the achievement of MSS indicators varies and has not yet produced a significant impact on improving service quality and patient safety. This study concludes that the success of MSS implementation is more strongly influenced by the robustness of supporting systems rather than individual commitment alone. Therefore, strengthening information systems, continuously enhancing human resource capacity, and implementing follow-up action plans based on quality improvement cycles are essential to improve compliance with standards and achieve MSS indicators optimally.